Illness cognition and depression among patients with coronary heart disease - Nuraeni, Aan; Anna, Anastasia; Praptiwi, Atlastieka; Nurhamsyah, Donny (Belitung Nursing Journal, 2021)
Background: Depression is a significant predictor of the quality of life among patients with coronary heart disease. Therefore, it is essential to explore the factors associated with depression. Illness cognition is considered one of the factors affecting depression. However, the relationship between illness cognition and the incidence of depression among Indonesian patients have not been widely investigated.Objective: This study aimed to investigate the correlation between illness cognition, consisting of the acceptance, perceived benefits, and helplessness variables, and depression in patients with coronary heart disease. Methods: This study employed a correlational research design with a total of 106 patients undergoing treatment at a hospital in West Java, Indonesia, selected using convenience sampling. Data were collected using a demographic questionnaire, Beck-Depression Inventory-II (BDI-II), and ICQ (Illness-Cognition Questionnaire). Data were analyzed using mean (SD), median, frequency distribution, and Spearman-rank. Results: 72% of respondents had no depression. Nevertheless, mild, moderate, and major depression suffered by 15%, 9%, and 4% of respondents, respectively. In terms of illness cognition, patients scored higher within the perceived benefits dimension (mean 20.13, SD 3.05), followed by acceptance (mean 18.22, SD 3.33) and helplessness (mean 13.20, SD 4.77), respectively. Furthermore, helplessness was significantly associated with depression (p <.01) with a positive correlation coefficient (r). Also, all items on the helplessness dimension had a significant correlation (p <.01) with depression accompanied by a positive r-value. Conclusion: Helplessness had a significant relationship with depression. So, cardiovascular nurses can anticipate depression in patients by making nursing interventions that can decrease the patients’ feelings of helplessness. Thus, factors that reduce helplessness need to be explored and taken into accounts in the treatment of patients with coronary heart disease.